Tunisia : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Tunisia showed strong performance owing to its prudent macroeconomic stance, aimed at continued fiscal consolidation and disinflation, backed by a solid record of investment in social and physical infrastructure. The paper describes the government finances, structure of the nonfinancial public sector, and reviews the real, monetary, financial, and external sector developments. The study found that considerable progress was made on the fiscal front, and in implementing tax measures not only to offset the decline in trade taxes but also to tighten expenditure to compensate for the decline in nontax revenue.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet